Solving Discrete Ordered Median Problems with Induced Order - Domínguez-Merino, Enrique; Marín, Alfredo (My University, 2020)
Ordered median functions have been developed to model flexible discrete location problems. A weight is associated to the distance from a customer to its closest facility, depending on the position of that distance relative to the distances of all the customers. In this paper, the above idea is extended by adding a second type of facility and, consequently, a second weight, whose values are based on the position of the first weights. An integer programming formulation is provided in this work for solving this kind of models.
Keywords: Análisis posicional; ordered median problem; optimization; location analysis